Effects of molecular hydrogen supplementation on fatigue and aerobic capacity in healthy adults: A systematic review and meta-analysis - Zhou, Kaixiang; Liu, Meng; Wang, Yubo; Liu, Haoyang; Manor, Brad; Bao, Dapeng; Zhang, Luyu; Zhou, Junhong (Frontiers in Nutrition, 2023)
Background Fatigue is oftentimes induced by high-intensity exercise potentially via the exceeded amount of reactive oxygen species, leading to diminished functions (e.g., aerobic capacity) and increased risk of injuries. Studies indicate that molecular hydrogen (H2), with antioxidant and anti-inflammatory properties, may be a promising strategy to alleviate fatigue and improve aerobic capacity. However, such effects have not been comprehensively characterized. Objective To systematically assess the effects of in taking H2 on fatigue and aerobic capacity in healthy adults. Methods The search was conducted in August 2022 in five databases. Studies with randomized controlled or crossover designs that investigated the rating of perceived exertion (RPE), maximal oxygen uptake (VO2max), peak oxygen uptake (VO2peak), and endurance performance were selected. The data (mean ± standard deviation and sample size) were extracted from the included studies and were converted into the standardized mean difference (SMD). Random-effects meta-analyses were performed. Subgroup analysis was used to analyze potential sources of heterogeneity due to intervention period, training status, and type of exercise. Results Seventeen publications (19 studies) consisting of 402 participants were included. The pooled effect sizes of H2 on RPE (SMDpooled = −0.38, 95%CI −0.65 to −0.11, p = 0.006, I2 = 33.6%, p = 0.149) and blood lactate (SMDpooled = −0.42, 95% CI −0.72 to −0.12, p = 0.006, I2 = 35.6%, p = 0.114) were small yet significant with low heterogeneity. The pooled effect sizes of H2 on VO2max and VO2peak (SMDpooled = 0.09, 95% CI −0.10 to 0.29, p = 0.333, I2 = 0%, p = 0.998) and endurance performance (SMDpooled = 0.01, 95% CI −0.23 to 0.25, p = 0.946, I2 = 0%, p > 0.999) were not significant and trivial without heterogeneity. Subgroup analysis revealed that the effects of H2 on fatigue were impacted significantly by the training status (i.e., untrained and trained), period of H2 implementation, and exercise types (i.e., continuous and intermittent exercises). Conclusions This meta-analysis provides moderate evidence that H2 supplementation alleviates fatigue but does not enhance aerobic capacity in healthy adults. Systematic review registration www.crd.york.ac.uk/PROSPERO/, identifier: CRD42022351559.